The Analysis of Lecturers Information Literacy Skill to Support Competence in Teaching Learning Activities - Saryanto Saryanto; Andi Saadillah; Muthia Mutmainnah; Devin Mahendika; Enny Diah Astuti (Journal on Education, 2023)
The purpose of this study is to evaluate the information literacy lecturers' ability to search for information and to determine how information literacy is used by institutional lecturers to enhance professionalism and competency in the teaching process. This study used a descriptive methodology combined with a qualitative research strategy. The information for this study was gathered by observation, interviews, and a review of the literature. The findings of this study suggest that information literacy educators should continue to advance. The information is sound from the perspective of understanding the necessity of lecturers in educational settings. This is so that they can more effectively fulfill their duty as a lecturer and continue to grow professionally. The ability of informants to retrieve information is still in the early stages of development. An improved ability to search for information is necessary for the advancement of information technologies. The instructor's information use skills are adequate. This is evident in how he or she creates the course modules, syllabi, etc. Overall, the information literacy that instructors in colleges possess is good and simply need little facility development. Because research faculty and librarians have been able to work together to develop a literate generation of information, collaboration amongst the entire campus community also needs to be strengthened.